Comparison Analysis of Plaster Aci Wall Finishing Method With Stick on Wall - Rahmad Wahyudi (NAROTAMA UNIVERSITY, Indonesia, 2022)
With the development of technology in the world of building materials, it is demanded that related parties include stakeholders to be able to respond and think effectively and efficiently which of course can be harmonized with the motto of the construction world, namely BMW (cost, quality, time) as well as the demands for the speed of construction projects causing manufacturers to materials compete to create new materials that can speed up the building construction process. Today a lot of products are popping up as a result of innovative creative ideas in order to compete to be the best. For the current building material products that have been and or are on the rise, one of them is the development of technology regarding wall finishing work. The wall is one of the non-structural elements in buildings, both low-rise and high-rise buildings must use this material. Wall finishing work usually uses wall plaster. Wall plaster on lightweight bricks is generally a mortar that has been mixed during the manufacturing process with a formulation that has been tested so that it has better properties than sand cement mortar which is generally mixed in the field, easy to use just by adding enough water and stirring until evenly distributed manually or by machine. stirrer. (license brochure, plaster). However, in recent years there have been developments in wall plastering materials, the emergence of gypsum walls which is a new material as an alternative to lightweight brick plastering in wall construction. This gypsum wall innovation is known for being faster and cheaper but has shortcomings in terms of quality and durability when compared to plastering. In this study the authors review the wall finishing work on the Grand Sungkono Lagon Apartement project which is located on Jl. KH Abdul Wahab Siamin. Where in this project using wall finishing in the form of stucco and stick on wall (gypsum wall). This became the basis of the research, namely by comparing wall plastering using aci plaster with wall plastering replaced using gypsum (stick on wall). The goal to be achieved in writing this scientific paper is to find out which method of construction of wall work is more efficient between the two methods of wall plastering and replacement of wall plastering.